New National Initiatives of Modernizing Education in China. (September 2019) - Zhu, Yiming
Purpose: This article aims to shed light on a latest education policy blueprint in China, titled China's education modernization 2035, which was issued by the Central Government of China in February of 2019. Design/Approach/Methods: This is an analytical policy review. Findings: The author argues that this new Chinese educational policy was driven by three factors: UN 2030 Agenda, China's national strategy, and Chinese educational reform and improvement. In China's education modernization 2035, eight key principles were rooted in the Chinese context and also recognized by international society. According to this policy initiative, 10 specific strategical tasks are outlined to reform Chinese education toward 2035. Originality/Value: The article will be useful to learn and understand the new directions and the future approaches of Chinese education development and reform toward 2035.